Innovative Production of Bioproducts From Organic Waste Through Solid-State Fermentation - Cerda, Alejandra; Artola, Adriana; Barrena, Raquel; Font, Xavier; Gea, Teresa; Sánchez, Antoni (Frontiers in Sustainable Food Systems, 2019)
Solid-state fermentation (SSF) is, by definition, a technology carried out in absence or near absence of free water. Therefore, it allows the use of solid materials as substrates for further biotransformation. SSF has gained attention in the last years being reported as a promising eco-technology that allows obtaining bioproducts of industrial interest using solid biomass (wastes and by-products). Main advantages over conventional submerged fermentation rely on the lower water and energy requirements, which generate minimum residual streams. However, drawbacks related to poor homogeneity and energy and mass transfer often appear, hindering the process yield and the downstream of the produced bioproducts. Despite the difficulties, many successful processes have been reported on the production of a variety of bioproducts such as hydrolytic enzymes, mostly carbohydrases for bioethanol production, and to a lesser extent, aromas, biosurfactants, biopesticides, bioplastics, organic acids or phenolic compounds. Most of the reported research focuses on process development at small scale; however, the main challenges to overcome in SSF are related to the upscaling and the development of a consistent and continuous operation. In this work, the main advances for the production of valuable/innovative bioproducts are presented and discussed.